Efficacy and safety of subcutaneous trastuzumab and intravenous trastuzumab as part of adjuvant therapy for HER2-positive early breast cancer: Final analysis of the randomised, two-cohort PrefHer study. (November 2017) - Pivot, X.; Verma, S.; Fallowfield, L.; Müller, V.; Lichinitser, M.; Jenkins, V.; Sánchez Muñoz, A.; Machackova, Z.; Osborne, S.; Gligorov, J.; ,
Abstract: Aim: To assess efficacy (event-free survival, EFS) and safety in patients followed up for 3 years in the PrefHer study (NCT01401166). Patients and methods: Post surgery and post chemotherapy in the (neo)adjuvant setting, patients with human epidermal growth factor receptor 2 (HER2)-positive early breast cancer were randomised to receive four cycles of the subcutaneous form of trastuzumab (Herceptin ® SC [H SC] via single-use injection device [Cohort 1] or delivery via a hand-held syringe from an SC Vial [Cohort 2]; 600 mg fixed dose) followed by four of the intravenous form of trastuzumab (Herceptin ® [H IV]; 8 mg/kg loading, 6 mg/kg maintenance doses) in the adjuvant setting or vice versa every 3 weeks. Patients could have received H before randomisation. H was then continued to complete a total of 18 cycles, including any cycles received before randomisation. Results: A total of 488 patients were randomised across both cohorts. After median follow-up of 36.1 months, 3-year EFS across both groups in the evaluable intention-to-treat population (467 patients) was 90.6% overall, 89.9% in Cohort 1, and 91.1% in Cohort 2. No new safety signals were identified during long-term follow-up, with only one cardiac serious adverse event in the safety population (483 patients). Conclusions: Three-year EFS data following H SC and H IV treatment are consistent with those reported by previous trials for H in the adjuvant setting. The overall safety profile during adjuvant treatment was as expected. Highlights: 3-year event-free survival data in PrefHer were consistent with previous trials. The overall safety profile during adjuvant treatment was as expected. H SC was well tolerated and no new safety signals were identified.